Citizens' Rights and the Right to Be a Citizen - Ballin, Ernst Hirsch (Brill, 2025)
Ernst Hirsch Ballin discusses the significance of citizens’ rights against the backdrop of ongoing migration and urbanization in the beginning of the 21st century. The traditional view that each state has the sovereign power to give or withhold citizenship, puts the full enjoyment of human rights at risk whenever exclusion is based on differences in nationality. Citizens’ rights are the essential connecting link between human rights and life in a democratic society. Citizens have an individual right, as a citizen, to take part in the democratic process and in the structures of solidarity of the state where they are effectively at home. By recognizing everyone’s right to the citizenship of the state in which they can make these rights a reality, citizens’ rights can bridge the gap between the universality of human rights and the changing political and social settings of people’s lives. Limits on dual citizenship are counterproductive, European citizenship paves the way for transnational citizenship.